Frequency of Endometriosis among Infertile Women on Diagnostic Laparoscopy - Shabir, Nousheena Akhter (International Journal of Pathology, 2019)
Introduction: A condition in which there is failure of conceiving child after frequent sexual intercourse that is unprotected for 12 months or more is known as infertility. A variety in clinical presentation, difficult diagnosis and management makes endometriosis a challenging medical problem. Clinical information related to ovarian and tubal status, normality of uterine and some proper procedure for diagnosis of many pelvic pathological conditions such as pelvic inflammation, pelvic congestion, endometriosis and tuberculosis can be obtained by laparoscopy. Objective: To determine the frequency of endometriosis on diagnostics laparoscopy in females with infertility. Material & Methods: This cross-sectional study was done at the department of Obstetrics & Gynecology Combined Military Hospital (CMH) Muzaffarabad, Azad Kashmir to determine the frequency of endometriosis on diagnostics laparoscopy in infertile women. The duration of the study was 6 months (from October 30, 2016 to April 30, 2017). The participants were taken had age 18-45 years with primary complain of primary or secondary infertility were subjected to diagnostic laparoscopy and were diagnosed to have endometriosis as the cause of infertility were included in the study. Sample size for the study was taken by non-probability, consecutive sampling of 170 females. Data from 82 female undergoing diagnostic Laparoscopy meeting inclusion criteria was taken from department of Obstetrics & Gynecology. After taking informed written consent basic demographical details like age, name and contact details were taken. A clinical examination was carried out during patient’s inclusion. The quantitative data like age and duration of infertility were reported in Mean ± S.D while the categorical data like type of infertility and endometriosis were reported in Frequency (%). To address effect modifiers data was stratified for female’s age, duration of infertility and types of infertility (primary or secondary). Post stratification Chi-square test was used considering, p-value ≤ 0.05 as significant. Results: The mean age of cases in this study was 31.56±8.19 years with mean duration of infertility was 10.16±5.05 months. There were 36(21.18%) who had < 6 months and 134(78.82%) cases had ≥ 6 months of duration of disease. There were 76(44.71%) cases that had primary and 94(55.29%) cases had secondary infertility. According to operational definition a total of 23(13.53%) cases had endometriosis. Conclusion: The frequency of endometriosis in females with infertility is considerably higher. In future these females can be prevented from endometriosis by early screening and with appropriate medication.